P142. Pushing the limit of sensitivity for non-invasive high-frequency EEG: Recording human single-trial spike-like SEP in noisy environments. Issue 8 (August 2015) - Waterstraat, G.; Scheuermann, M.; Burghoff, M.; Fedele, T.; Curio, G.
<x xml:space="preserve">Abstract</x> Introduction Human high-frequency EEG responses evoked by median nerve stimulation are non-invasive markers of cortical population spikes. For long, their reliable detection required averaging thousands of trials. Recently, low-noise EEG amplifiers combined with extensive electro-magnetic shielding allowed for a sensitive single-trial non-invasive detection of human high-frequency SEP. Here, using as few as 8 standard surface electrodes we demonstrate how specialized neurotechnology and offline analysis can achieve single-trial hf-SEP recordings without elaborate shielding. Methods In 6 healthy male subjects, 8 sintered Ag/AgCl surface EEG electrodes (reference at nose) were distributed above the left somatosensory cortex with impedances at about 1 kOhm. EEG was recorded upon right median nerve stimulation using a custom-built CE-certified low-noise EEG amplifier, specifically engineered to insulate the EEG from electromagnetic interferences. The signal was filtered spectrally and spatially (canonical correlation analysis variant) and transformed to the time–frequency domain (S transform). Results Bursting activity at about 600 Hz ('σ-burst') in response to median nerve stimulation was detectable in all six subjects, both in the average SEP and in the average time–frequency-transform of single-trial responses. Moreover, this approach allowed to analyze the intrinsic single-trial variability of the hf-SEP. Significance Using tailor-made neurotechnology, evoked human cortical population spikes can be measured non-invasively in single-trial EEG without elaborate shielding and using a small number of standard surface electrodes, thus enabling clinical applicability.